Induced sample via transient isotachophoresis mediated with sweeping in micellar electrokinetic chromatography for the dual-stacking strategy of non-steroidal anti-inflammatory drugs in environmental water samples - Semail, Nadhiratul Farihin; Abdul Keyon, Aemi Syazwani; Saad, Bahruddin; Kamaruzaman, Sazlinda; Mohamad Zain, Nur Nadhirah; Lim, Vuanghao; Miskam, Mazidatulakmam; Wan Abdullah, Wan Nazwanie; Raoov, Muggundha; Yahaya, Noorfatimah (Elsevier, 2022)
Realising the need to devise a simple, sensitive, and reliable detection method, this study investigated the development of a dual-stacking transient isotachophoresis (t-ITP) and sweeping in micellar electrokinetic chromatography with diode array detector (t-ITP/sweeping-MEKC-DAD) for the determination of selected non-steroidal anti-inflammatory drugs (NSAIDs); ketoprofen, diclofenac and naproxen from aqueous matrices. Prior to the system setup, various parameters were optimised to assess the potential use of the t-ITP paired with the sweeping stacking technique in micellar background electrolyte for dual preconcentration and separation of trace amounts of NSAIDs. Once the optimum conditions have been established, the method performance was validated and applied to 17 environmental water samples. Based on the results, the combined t-ITP and sweeping approach significantly improved the stacking and separation sensitivity. A large volume of samples could also be introduced and subsequently separated by MEKC with greater focusing effects due to the sweeping. Under optimised conditions, the developed method exhibited excellent linearity at a high range (0.1–500 ng/mL, r2 ≥ 0.998), low limits of detection (LODs) of 0.01–0.07 ng/mL, and a remarkable relative recovery (RR) of 99.6–101.9% with a relative standard deviation (RSD) of 1.4–8.6% (n = 9). Ultimately, the sensitivity enhancement factors improved up to 666-fold using the optimised method. Therefore, the proposed method presents a simplified yet effective and suitable for the determination of NSAIDs from aqueous matrices.